Evaluating the Effectiveness of Primary Care Health Checks at Assessing Cardiovascular Risks among Ethnic Minorities in the UK: A Systematic Review - Aleesha Karia; Reza Zamani; Tanimola Martins; Abdal Zafar; Ava Zamani (Reviews in Cardiovascular Medicine)
Background: Cardiovascular diseases (CVD) affect around 7.6 million people in the UK, disproportionately affecting the minority ethnic community. In 2009, the UK's National Health Service (NHS) launched a Health Check (NHSHC) scheme to improve early diagnosis of various clinical conditions, including CVD, by screening patients for associated risk factors. This systematic review investigated the engagement of minority ethnic groups with these services. Methods: Seven studies identified patient demographics of NHSHC attendees using the Preferred Reporting Items for Systematic And Meta Analysis-Diagnostic Test Accuracy (PRISMA-DTA) guidelines and accessing Ovid (MEDLINE), PubMed and Web of Science databases. Results: The screening was either by invitation or opportunistic at other appointments with their doctor. Engagement with the service was highest among the South Asian patients (21%–68%), but lowest amongst Chinese patients (12%–61%). Further, engagement was lower among those screened following a formal invitation than those seen opportunistically. However, a greater proportion of patients were screened opportunistically than by invitation. Conclusions: Overall, we found that the NHSHC is not being utilised adequately for all patients at high risk of CVD, particularly White and Chinese patients. It highlights the critical role of primary care could play to improve patient engagement with the service.